Design and implementation of web-based expert tool for selection of climate resilient rapeseed-mustard varieties (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard grown area in India has been classified into five major agro-ecological zones. The basic climatic conditions targeted for developing the resource efficient varieties are rainfed and irrigated. Approximately 30% of total rapeseed-mustard cultivated area in the country is rainfed. In situations of erratic climatic conditions, it is imperative for the farmers to be well informed about the available technologies suitable for their regions. In India, rapeseed-mustard researchers have developed many improved varieties performing well in both rainfed & irrigated conditions. However, information about these varieties is scattered and in several forms. The challenge was to organize the information electronically so that the farmers of the country could be benefited from this information. For this purpose, a web based expert system for rapeseed-mustard crop variety selection was developed by applying knowledge engineering approaches with scientific knowledge base in backend. The system suggests the varieties of farmer’s/advisors’s choice based on agro-climatic conditions. The system carries detailed information about 160 notified varieties that have been stored in its knowledge base. The important feature implemented in this expert system is that it is bilingual and available in English and Hindi languages making it easily understandable by farmers of the major rapeseed-mustrad grown states.